Insights on the Scientific Publications of the Faculty of the College of Science, UP Diliman: 1998-2017 - David, Carlos Primo C.; Geronia, Mart Cyrel M. (Science Diliman: A Journal of Pure and Applied Sciences, 2020)
This paper compiles all the scientific publications from UP College of Science (UP Science) as indexed in both Thomson Reuters’ Web of Science and Scopus from 1998 to 2017. This research follows a previous study that used journal publications as a measure to track the scientific productivity of UP Science. Likewise, this paper only considered publication output as the sole criterion used for academic productivity. A total of 2,295 unique journal publications or 54% of all indexed publications from the University of the Philippines Diliman come from UP Science. On average, UP Science increases its publication output by about eight articles each year with a total of 208 journal articles in 2017. Since 2013, UP Science has attained the benchmark of one publication per Ph.D. faculty per year. In addition to analyzing the document count per institute, efforts to distill the data and come up with additional insights on what drives productivity were done. From the dataset, more than half of the papers are a result of collaborations with foreign institutions. Opportunities for collaborations with other Higher Education Institutions and within UP Science remain low and should be capitalized on. Publications in prestigious journals are also slightly increasing and may be included as another metric to track. Aggregate and mean h-index for institutes also corroborates scientific productivity and impact of many institutes within UP Science. Lastly, insights on individual faculty productivity clearly shows the shift from primary researcher to mentor between their 6th to 15th year as faculty member. This highlights the potential role of graduate student publication as yet another strategy to increase UP Science’s research output.
Keywords: UP Science, publication record, scientific productivity, institutional collaborations, mean h-index, research impact